Impact of Inflation, CO2 Emissions and Foreign Investment on Economic Growth: A Case of Pakistan - Hussain, Sadam; Ahmad, Waqar; Qamar, Yasmeen; Akram, Muhammad Shahid (Asian Development Policy Review, 2019)
In this article, an endeavor has been made to break down the connection and the impact of foreign investment together with CO2 emission, labor, capital and inflation on economic growth of Pakistan by utilizing time series data from 1971-2015. Since it's alluring to test the effect of foreign investment inflow utilizing the ongoing actualities and figure, the examination utilizes GDP as needy variable while FDI, CO2, and inflation are utilized as free variables. The examination adopts ARDL to Co-integration techniques for the experimental investigation. The exact estimations demonstrate that foreign investment has positive and huge relationship with economic growth which infers that foreign investment and capital support economic growth both in short and long run. The CO2 discharges have negative and critical connection with economic growth in long run however hold insignificant in short runs. Increment in inflation impedes the economic growth in long run on account of the negative connection among GDP and inflation. These experimental bits of knowledge give policy-makers essential strategy recommendations.